Morphogenesis of Ophelimus maskelli (Hymenoptera: Eulophidae) gall induction in Eucalyptus tereticornis and comparison with other eucalyptus gall-inducing insects - González, Ana María (2025)
Gall-inducing insects can severely impact Eucalyptus plantations, causing premature leaf senescence, defoliation, and reduced tree growth. Although the gall formation of various hymenopteran species associated with Eucalyptus has been studied, the morphogenesis of Ophelimus maskelli (Hymenoptera: Eulophidae) galls remains poorly understood. This study characterizes the anatomical and developmental processes of O. maskelli galls and compares them with reported changes those induced by Leptocybe invasa, Ophelimus eucalypti, and Ophelimus migdanorum. Leaf samples, both galled and non-galled, were collected from Eucalyptus tereticornis plantations in Argentina. Galls were classified according to their developmental stage and analysed using histological techniques, including light and scanning electron microscopy. Ophelimus maskelli galls were monothalamous and confined to the leaf blade. Their development involved hyperplasia, mesophyll thickening, and the differentiation of nutritive tissue and a protective sclerenchyma layer. Structurally, they exhibited an intermediate level of complexity. This study provides detailed anatomical and structural insights into the morphogenesis of O. maskelli galls, serving as a basis for future research on Ophelimus species and their parasitoids in Eucalyptus plantations.